The magic of Latin dancing [videorecording (DVD)] : capture the magic and learn to dance from the pros. - Mason, Teresa; Turley, Kyle; Turley, Heather (Heather Menard Turley) (Kultur, 2012)
Presents a comprehensive introduction to Latin dancing, featuring Teresa Mason's method to teach beginning-, intermediate-, and advanced-level dancers; covering the merengue, rumba, cha cha, salsa, and samba; and discussing frame, leading, Latin dance positions, and related topics with tips and advice from Teresa Mason.